PORÓWNANIE PRZYZWYCZAJEŃ ŻYWIENIOWYCH ZAWODNIKÓW W PŁYWANIU I LEKKIEJ ATLETYCE W WIEKU 18-20 LAT (Physical Culture and Sport: Scientific Perspective, 2023)
Proper nutrition is one of the many factors that influence sports success. Regular training, proper regeneration and taking care of your general health are also important. Nutritional habits in athletes are important to optimally achieve physical performance and support body recovery. Athletes should provide the body with the right amount of calories and nutrients to meet the increased energy needs. Properly balanced diet - nutrients such as proteins, carbohydrates and fats should be supplied in the right proportions. Also, staying hydrated is crucial for athletes, who should drink enough water before, during and after exercise to compensate for fluid loss during exercise. Players often sleep too little, which negatively affects training progress, they have bad habits of hydration, which also contributes to poorer results and poor well-being. The authors of this study at the XVIІІ International Scientific Conference "Modelling and information technologies in physical education and sport" at the Lviv State University of Physical Culture named after Ivan Boberskyj (September 21-23, 2023) - presented in the panel: Modeling of objects and processes in biological and natural systems - two theses presenting their pilot scientific research: 1) Nutritional habits of athletes - swimmers aged 18-20 (research conducted in 2021), 2) Nutritional habits of athletes - athletes aged 18-20 (research conducted in 2022) ). It might seem that the way of eating while exercising is a very simple matter. Unfortunately, it turns out that this is a very important skill consisting in planning and testing various nutritional variants, often in close cooperation with a sports club nutritionist. In this study, the authors will carry out a comparative analysis of pilot studies - habits, eating habits of swimming and athletics athletes. Athletes are a group of people who perform a lot of physical effort, which means that they have a very high demand for carbohydrates, fats and proteins. The greater the training intensity, the greater the demand for sugars and amino acids. However, the lower the intensity, the more fats play a role. In order for the body to be able to withstand training loads, it must have adequate amounts of carbohydrates. That is, the greater the effort, the greater the demand for energy, balanced energy.
Keywords: analysis; supplementation; health; sport; meal; athlete